Pengaruh Sarana Prasarana Dan Disiplin Kerja Terhadap Kinerja Pegawai Di Dinas Pendidikan Dan Kebudayaan Provinsi Lampung - Sungkowo, Ari; Ahiruddin, Ahiruddin (Utami Publisher, 2025)
An organization is formed to achieve a common goal, but to achieve the goal effectively, good and correct management is needed. For this purpose, the necessary resources are designed, including natural resources, capital resources, human resources, technology and work mechanisms to achieve organizational goals.Apart from the function and role of human resources, achieving smooth work also relies heavily on effective management facilities and systems. Without facilities and infrastructure, it is impossible for an institution's goals to be achieved. Therefore, an institution needs office facilities and infrastructure that can facilitate employees in carrying out their duties and work so that administrative activities and other operational activities can run smoothly. The availability of sufficient office facilities of good quality is an important part that needs to be prepared optimally and continuously so as to ensure the smooth running of employee work activities.The aim of this research is to determine: 1. The influence of infrastructure on employee performance 2. The influence of work discipline on employee performance 3. The influence of infrastructure and work discipline together on the performance of employees of the Education and Culture Office of Lampung Province.This research uses a quantitative descriptive research method, namely a research method that uses data in the form of numbers to analyze the facts found which aims to determine the relationship between variables in a population. The analysis used is simple and multiple regression. This research used 25 respondents.Based on the results of data analysis, the hypothesis answer was found as follows; There is an influence of Infrastructure (X1) on employee performance (Y) at the Lampung Province Education and Culture Office, with an influence level (R-square) of 72.8%. There is an influence of Work Discipline on employee performance at the Education and Culture Office of Lampung Province with an influence level of 81.2%. There is an influence of Infrastructure and Work Discipline together on employee performance at the Education and Culture Office of Lampung Province, with an influence level of 85.6%.